Effect of electron irradiation exposure on phase formation, microstructure and mechanical strength of Bi2Sr2CaCu2O8 superconductor prepared via co-precipitation method - Mohiju Z.; Hamid N.A.; Abdullah Y.; Kannan V. (American Institute of Physics Inc., 2023)
In this work the effect of electron irradiation on the mechanical properties of Bi2Sr2CaCu2O8 (Bi-2212) superconductor was studied by exposing the Bi-2212 superconductor with different doses of electron irradiation. Bi-2212 samples were prepared by using co-precipitation method. Irradiation was performed with irradiation dose of 100 kGray and 200 kGray, respectively. Characterization of the samples was performed by using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). Instron Universal Testing machine was used to measure the strength of the samples. The XRD patterns for the non-irradiated and irradiated samples show well-defined peaks of which could be indexed on the basis of a Bi-2212 phase structure. XRD patterns also indicate that electron irradiation did not affect the Bi-2212 superconducting phase. SEM micrographs show disorientation in the texture of the microstructure for irradiated samples. Sample exposed to 200 kGray electron irradiation dose shows enhancement of grain size. Their grain growth and texture improved slightly compared to other sample. The results also show that enlargement of grain size resulted in higher mechanical strength. 2015 AIP Publishing LLC.